The impact of Eco-innovation Drivers on Environmental Performance: Empirical Results from the Green Technology Sector in Malaysia - Fernando, Yudi; Wen, Xin Wah (Elsevier Ltd, 2017)

(untitled)
Cleaner production has become necessary to create resource-efficient production, as societies have become increasingly concerned with environmental issues. This paper develops a theoretical structural model representing the impact of five latent variables of eco-innovation drivers on the environmental performance. The conceptual framework is empirically tested based on a survey of Malaysian green tech companies. The results suggest that compliance with environmental regulations is the strongest predictor in the model. Market focus and technology used were confirmed as drivers that impact environmental performance positively. This paper concludes that the values of eco-innovation allow companies to counter challenges from competitors in the marketplace.